2019
DOI: 10.1002/ece3.5324
|View full text |Cite
|
Sign up to set email alerts
|

A burrowing ecosystem engineer positively affects its microbial prey under stressful conditions

Abstract: Species that facilitate others under stressful conditions are often ecosystem engineers: organisms that modify or create physical habitat. However, the net effect of an engineering species on another depends on both the magnitude of the direct interactions (e.g., competition or predation) and the specific environmental context. We used a laboratory system to isolate the trophic and engineering impacts of a predator, the nematode Caenorhabditis remanei … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…This study provides empirical support for the SGH and complements recent research using terrestrial animal communities that found evidence of increased importance of associative or facilitative interactions in harsh environments (Bell & Cuddington, 2019;Dangles et al, 2018;García-Navas et al, 2021). Additionally, by demonstrating that some taxa associate strongly with colony trees in more arid climates, we provide support that facilitation by weaver colonies increases the realized niches of certain species (Armas et al, 2011;He & Bertness, 2014).…”
Section: Colony Use Across a Spatial Gradientsupporting
confidence: 83%
See 1 more Smart Citation
“…This study provides empirical support for the SGH and complements recent research using terrestrial animal communities that found evidence of increased importance of associative or facilitative interactions in harsh environments (Bell & Cuddington, 2019;Dangles et al, 2018;García-Navas et al, 2021). Additionally, by demonstrating that some taxa associate strongly with colony trees in more arid climates, we provide support that facilitation by weaver colonies increases the realized niches of certain species (Armas et al, 2011;He & Bertness, 2014).…”
Section: Colony Use Across a Spatial Gradientsupporting
confidence: 83%
“…Additionally, by demonstrating that some taxa associate strongly with colony trees in more arid climates, we provide support that facilitation by weaver colonies increases the realized niches of certain species (Armas et al, 2011; He & Bertness, 2014). Furthermore, only one other study has extended this hypothesis to free‐ranging animals (García‐Navas et al, 2021), as many of the previous studies were tested under laboratory conditions (Bell & Cuddington, 2019; Dangles et al, 2018). Temporal variations in climatic conditions may also play a part in understanding the facilitative role of weaver colonies.…”
Section: Discussionmentioning
confidence: 99%
“…Non‐consumptive effects on prey communities and ecosystem processes are particularly expected when focal organisms driving those effects are both ecosystem engineers and predators (Bell & Cuddington, 2019; Majdi et al., 2014; Romero et al., 2015). Other non‐consumptive effects that might have contributed to our results include sediment reworking resulting from the burrowing behaviour of C. boltonii (de Nadaï‐Monoury et al., 2014), as well as nutrient excretion differences among individuals (Ngai & Srivastava, 2006; Vanni, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Non-consumptive effects on prey communities and ecosystem processes are particularly expected when focal organisms driving those effects are both ecosystem engineers and predators (Bell & Cuddington, 2019;Majdi et al, 2014;Romero et al, 2015).…”
Section: Mediation Of Predator Effects On Basal Resources By Inverteb...mentioning
confidence: 99%